2020
DOI: 10.1111/gcb.15057
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment of relationships between climate and tree growth

Abstract: Tree-ring records provide global high-resolution information on tree-species responses to global change, forest carbon and water dynamics, and past climate variability and extremes. The underlying assumption is a stationary (time-stable), quasilinear relationship between tree growth and environment, which however conflicts with basic ecological and evolutionary theory. Indeed, our global assessment of the relevant tree-ring literature demonstrates non-stationarity in the majority of tested cases, not limited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 48 publications
(95 reference statements)
12
115
0
Order By: Relevance
“…Our results showed that the relationships between climate, forest structure, demography and productivity were non-stationary due to climatic and forest structural changes. This result is in line with Wilmking et al (2020) in which they observed that tree growth responses to climate are generally non-stationary. We found that 80% of all SEM paths changed from 23SFI to 34SFI, Westoby, 1984).…”
Section: Climate Forest Structure Demography and Productivity Relsupporting
confidence: 91%
“…Our results showed that the relationships between climate, forest structure, demography and productivity were non-stationary due to climatic and forest structural changes. This result is in line with Wilmking et al (2020) in which they observed that tree growth responses to climate are generally non-stationary. We found that 80% of all SEM paths changed from 23SFI to 34SFI, Westoby, 1984).…”
Section: Climate Forest Structure Demography and Productivity Relsupporting
confidence: 91%
“…This body of evidence suggests more complex and nonlinear growth responses of trees to a changing climate, thereby leading to a decrease in year-to-year sensitivity of tree growth (i.e. "non-stationarity") in previously temperature-limited sites (D'Arrigo et al, 2008;Vaganov et al, 1999;Wilmking, 2005;Wilmking et al, 2020). Potential causes for this divergence include warming-induced thresholds of tree growth (D'Arrigo et al, 2004;Jochner et al, 2018), limitation of growth by nutrient availability (Fajardo and Piper, 2017) or drought stress (Büntgen et al, 2006) or interactions between these factors.…”
Section: Climate Warming Trend Analysis and The Divergence Problemmentioning
confidence: 99%
“…That is, the statistical relationship between ring‐width variation and the target climate variable is assumed to be stable over time. In the Anthropocene, an era of unprecedentedly rapid change of the Earth's climate system, this assumption is increasingly violated (Babst et al., 2019; Gustafson, 2013; Wilmking et al., 2020), and is even more likely to be violated in the future as the nonlinear increase in atmospheric evaporative demand with rising temperatures aggravates drought stress on trees. The extrapolation of past climate–growth relationships into conditions outside the domain of calibration may yield erroneous projections (Fritts, 1976).…”
Section: Introductionmentioning
confidence: 99%